Synthesis of 2-[4,5-dimethyl-1-(phenylamino)-1H-imidazol-2-ylthio]-N-(thiazole-2-yl)acetamide derivatives and their anticancer activities - Duran, Murat; Demirayak, Şeref (Springer Birkhauser, 2013)
In this work, 2-(4,5-dimethyl-1-(phenylamino)-1H-imidazol-2-ylthio)-N-(thiazol-2-yl) acetamide derivatives were synthesized by reacting 4,5-dimethyl-1-(phenylamino)-1H-imidazole-2(3H)-thione derivatives with some 2-chloro-N-(thiazol-2-yl)acetamide compounds. The structure of synthesized compounds was confirmed by IR, H-1 NMR, and mass spectra. Anticancer activities of the compounds selected by the National Cancer Institute were investigated by testing against a panel of 60 different human tumor cell lines derived from nine neoplastic cancer types. Compounds 7, 13, and 23 exhibited reasonable anticancer activity against the screened cancer types with relatively low GI(50) values. The compounds showed high activity against melanoma-type cell lines.
WOS: 000322181300007
Keywords: Imidazole; Thiazole; Anticancer; Melanoma; Acetamide